(untitled) (Ponti/Ponts. Langues, littératures, civilisations des pays francophone, 2025)
The aim of our research is to analyse the work of Clément Richer and its reception by Italian-speaking readers through the Italian translation of one of his novels, Ti-Coyo et son requin, published in 1941 and translated by Simona Martini in 1957 as Ti-Coyo e il suo pescecane. The story of the friendship between a child and a shark was so successful that it inspired the making of a film, Ti-Koyo e il suo pescecane. The screenplay was written by Italo Calvino and the film was made in collaboration with Folco Quilici. By analysing first the interlinguistic translation and then the intersemiotic translation, we reflect on how a work can be successful despite the translation process, which always involves a loss of meaning. A loss that must now be seen as a form of rebirth and new artistic creation. Two forms of translation are therefore at the heart of the work. They give rise to two distinct works, each indebted to the other in one way or another. We are therefore confronted with two artistic productions of equal value, each of which, in its own way, will have touched the sensibilities of the reader or viewer.